Workshop Pemberdayaan UMKM Di Desa Wonokerto Di Era 5.0 Menggunakan Strategi Digital Marketing - Siska Dewi; Anni Safitri; Kusuma Wijaya; Mukhsin Hadi; Ammilatuzzahro Ammilatuzzahro; Slamet Lutfi Maulana (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
This community service activity aims to overcome the problems of UMKM in Wonokerto village, Bandar sub-district. The main problems faced by UMKM players are packaging, lack of business permits, and digital marketing of products. This is the background for community service activities carried out by a team of accounting lecturers at the Institute of Technology and Science Nahdlatul Ulama Pekalongan. The theme of this service is the UMKM Empowerment Workshop in Wonokerto Village in the 5.0 Era Using Digital Marketing Strategies. The aim of this community service is to educate UMKM players about the concept of making attractive packaging, how to obtain business permits and how to market products digitally. The methods used in community service activities are field observation, preparing activity plans, creating activity materials, implementing activities as well as monitoring and evaluation. This service can open the minds of UMKM in Wonokerto village, Bandar sub-district, so that they can develop themselves through digital marketing training which can later improve economic prosperity in the future.